Working memory moderates the association between early institutional care and separation anxiety symptoms in late childhood and adolescence. (August 2019) - Alba, Laura Alicia; Flannery, Jessica; Shapiro, Mor; Tottenham, Nim
Abstract: Adverse caregiving, for example, previous institutionalization (PI), is often associated with emotion dysregulation that increases anxiety risk. However, the concept of developmental multifinality predicts heterogeneity in anxiety outcomes. Despite this well-known heterogeneity, more work is needed to identify sources of this heterogeneity and how these sources interact with environmental risk to influence mental health. Here, working memory (WM) was examined during late childhood/adolescence as an intra-individual factor to mitigate the risk for separation anxiety, which is particularly susceptible to caregiving adversities. A modified "object-in-place" task was administered to 110 youths (10–17 years old), with or without a history of PI. The PI youths had elevated separation anxiety scores, which were anticorrelated with morning cortisol levels, yet there were no group differences in WM. PI youths showed significant heterogeneity in separation anxiety symptoms and morning cortisol levels, and WM moderated the link between caregiving and separation anxiety and mediated the association between separation anxiety and morning cortisol in PI youth. Findings suggest that (a) institutional care exerts divergent developmental consequences on separation anxiety versus WM, (b) WM interacts with adversity-related emotion dysregulation, and (c) WM may be a therapeutic target for separation anxiety following early caregiving adversity.